2019
DOI: 10.1002/anie.201913640
|View full text |Cite
|
Sign up to set email alerts
|

f‐Element Half‐Sandwich Complexes: A Tetrasilylcyclobutadienyl–Uranium(IV)–Tris(tetrahydroborate) Anion Pianostool Complex

Abstract: Despite there being numerous examples of f‐element compounds supported by cyclopentadienyl, arene, cycloheptatrienyl, and cyclooctatetraenyl ligands (C5–8), cyclobutadienyl (C4) complexes remain exceedingly rare. Here, we report that reaction of [Li2{C4(SiMe3)4}(THF)2] (1) with [U(BH4)3(THF)2] (2) gives the pianostool complex [U{C4(SiMe3)4}(BH4)3][Li(THF)4] (3), where use of a borohydride and preformed C4‐unit circumvents difficulties in product isolation and closing a C4‐ring at uranium. Complex 3 is an unpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(105 citation statements)
references
References 64 publications
7
97
0
1
Order By: Relevance
“…We previously reported that reaction of [Li 2 {C 4 (SiMe 3 ) 4 }(-THF) 2 ] 12 with UCl 4 led to reduction of uranium(IV) to intractable mixtures of uranium(III)-containing products. 8 However, thorium(IV) has a far greater reduction potential (E q Th(IV) / Th(III) À3.7 V) than that of uranium(IV) (E q U(IV) / U(III) À0.6 V). 13 Nevertheless, addition of a solution of [K 2 {C 4 (SiMe 3 ) 4 }] 14 to [ThCl 4 (THF) 3.5 ] 15 resulted in oxidation of dianionic {C 4 (SiMe 3 ) 4 } 2À to the neutral cyclobutadiene {C 4 (SiMe 3 ) 4 }, 16 as conrmed by multinuclear NMR spectroscopy, and deposition of an insoluble dark grey precipitate presumed to be KCl and colloidal thorium.…”
Section: Synthetic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that reaction of [Li 2 {C 4 (SiMe 3 ) 4 }(-THF) 2 ] 12 with UCl 4 led to reduction of uranium(IV) to intractable mixtures of uranium(III)-containing products. 8 However, thorium(IV) has a far greater reduction potential (E q Th(IV) / Th(III) À3.7 V) than that of uranium(IV) (E q U(IV) / U(III) À0.6 V). 13 Nevertheless, addition of a solution of [K 2 {C 4 (SiMe 3 ) 4 }] 14 to [ThCl 4 (THF) 3.5 ] 15 resulted in oxidation of dianionic {C 4 (SiMe 3 ) 4 } 2À to the neutral cyclobutadiene {C 4 (SiMe 3 ) 4 }, 16 as conrmed by multinuclear NMR spectroscopy, and deposition of an insoluble dark grey precipitate presumed to be KCl and colloidal thorium.…”
Section: Synthetic Considerationsmentioning
confidence: 99%
“…Indeed, although transition metal cyclobutadienyl chemistry was established in the 1960s, 5 the rst f-elementcyclobutadienyl complex, an inverted sandwich tetraphenylcyclobutadienyl diuranium(IV) species, was reported in 2013. 6,7 Very recently, the uranium(IV)-cyclobutadienyl half sandwich pianostool complex [U{C 4 (SiMe 3 ) 4 }(BH 4 ) 3 ][Li(THF) 4 ] (A) was reported, 8 and shortly aer that four uranium(IV)-cyclobutadienyl complexes [U{C 4 (SiMe 3 ) 4 }(BH 4 ) 3 ][Na(12-crown-4)], 9 [U{C 4 -(SiMe 3 ) 4 }(BH 4 ) 2 (m-BH 4 ){K(THF) 2 }] 2 , 9 [U(BH 4 ){C 4 (SiMe 3 ) 4 }{k 3 -C 4 H(SiMe 3 ) 3 -k-(CH 2 SiMe 2 )}][Na( t BuOMe) 3.6 (THF) 0.4 ], 9 and [{U(C 4 [SiMe 3 ] 4 )(m-I) 2 } 3 {m 3 -O}][Mg(THF) 6 ] were disclosed. 10 These six uranium-cyclobutadienyl complexes constitute all actinidecyclobutadienyl chemistry to date, in stark contrast to the plethora of reported f-element h n -carbocyclic C 5-9 complexes.…”
Section: Introductionmentioning
confidence: 99%
“…To conclude, [27] we have prepared and characterised the first example of an f-element half-sandwich cyclobutadienyl complex, and indeed it is only the second example of an actinide-cyclobutadienyl complex. Whereas synthetic endeavours with UCl 4 have thus far been intractable,u sing the halide-free uranium(III)-tris(tetrahydroborate), itself an infrequently used class of complex in actinide chemistry, proved decisively fruitful.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Liddle's research interests include f‐block–ligand multiple bonding, metal–metal bonds, small‐molecule activation and catalysis, and single‐molecule magnetism. Among his most recent contributions to Angewandte Chemie are a Guest Editorial on lanthanide and actinide chemistry and a Communication in which he introduced a tetrasilylcyclobutadienyl–uranium half‐sandwich complex …”
Section: Awarded …mentioning
confidence: 99%